Pulmonary function and biceps brachial strength after phrenic or intercostal nerve transfer in brachial plexus injuries: systematic review - Moraes, Alexa Alves de (2022)
Introduction: Although there is evidence that transfers of intercostal (TIM) or phrenic (TFM) nerves to the musculocutaneous after traumatic brachial plexus injuries (LTPB) can promote declines in lung function, there is no consensus on which technique is best. more effective for biceps functional recovery, promoting less damage to lung function. Objective: To compare the pulmonary function of patients undergoing TIM or TFM after LTPB. Methodology: The searches were carried out in the MEDLINE/PubMed, LILACS, CINAHL, Scopus, Scielo, The Cochrane Librabry, Web of Science and Bank of Theses and Dissertations databases. Keywords used were brachial plexus, nerve transfer, phrenic nerve, intercostal nerves, pulmonary function and spirometry. Observational studies that presented data on pulmonary function, dyspnea, range of motion and muscle strength for elbow flexion in individuals with LTBP were included. The methodological quality of the studies was analyzed using the Newcastle-Ottawa Scale. Results: 14,104 studies were identified, of which seven were included in this review. Two studies showed favorable results for TIM in terms of lung function and six studies showed evidence of better bicipital functional recovery using this technique. The articles showed moderate methodological quality. Conclusion: Although TIM shows signs of being less harmful to pulmonary function and more effective for the recovery of muscle strength of the biceps brachii in relation to TFM, there is a need for studies with better methodological quality and that take into account experience and choice. of the surgeon.